The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1098/rsif.2012.0617
|View full text |Cite|
|
Sign up to set email alerts
|

A mechanistic model for bromodeoxyuridine dilution naturally explains labelling data of self-renewing T cell populations

Abstract: Bromodeoxyuridine (BrdU) is widely used in immunology to detect cell division, and several mathematical models have been proposed to estimate proliferation and death rates of lymphocytes from BrdU labelling and delabelling curves. One problem in interpreting BrdU data is explaining the de-labelling curves. Because shortly after label withdrawal, BrdU þ cells are expected to divide into BrdU þ daughter cells, one would expect a flat down-slope. As for many cell types, the fraction of BrdU þ cells decreases duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Division and death are normally quantified by following the accumulation and loss of cells labeled in vivo with BrdU or deuterium from heavy water or deuterated glucose, taken up by dividing cells during administration of label and diluted following its withdrawal (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). These experiments are typically performed over days to weeks and collectively have revealed that cell populations initially assumed to be homogenous may in fact comprise multiple subpopulations dividing and dying at different rates (kinetic heterogeneity) and/or that cells that are quiescent or have recently divided may have different susceptibilities to death (temporal heterogeneity).…”
mentioning
confidence: 99%
“…Division and death are normally quantified by following the accumulation and loss of cells labeled in vivo with BrdU or deuterium from heavy water or deuterated glucose, taken up by dividing cells during administration of label and diluted following its withdrawal (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). These experiments are typically performed over days to weeks and collectively have revealed that cell populations initially assumed to be homogenous may in fact comprise multiple subpopulations dividing and dying at different rates (kinetic heterogeneity) and/or that cells that are quiescent or have recently divided may have different susceptibilities to death (temporal heterogeneity).…”
mentioning
confidence: 99%
“…In this phase, separated peaks occur, but only at very low label intensities. These may, in real experiments, well lay below the detection threshold and thus not appear in the data [4]. …”
Section: Resultsmentioning
confidence: 99%
“…With this recursive definition and X (0) = 0, we arrive at X(i)MathClass-rel=MathClass-op ∑lMathClass-rel=1i2MathClass-bin-jUj for the label content after i divisions. Note: The special case of ptexteff(k)(x)MathClass-rel=δ(xMathClass-bin-μ) represents a uniform labeling value as used in previous models [4]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations